Psychological Problems of Patients with Colorectal Cancer - Khalaf, Ghalib; Tawfieq, Narmen (Iraqi National Journal of Nursing Specialties, 2013)
Objective: Assessment the psychological problems in patients with colorectal cancer, and to find out therelationship between socio-demographic characteristics such as (age, sex, marital status, educational level,and occupation) and psychological problems for those patients.Methodology: A descriptive design is employed through the present study from 1st July 2011 to 25th December2011 in order to study the quality of life in colorectal cancer patients with psychological problems.A purposive (non probability) sample is selected for the study which includes (60) patients diagnosed withcolorectal cancer were treated in Mosul Oncology and Nuclear Medicine hospital or the patients who visitedthe outpatient clinic in the same hospital for medical follow–up and further treatment. Data were gatheredthrough the patients` interviewed. Assessment questioner consist of two parts contains demographiccharacteristic, the other part concerning about assessment the psychological problems for patients withcolorectal cancer. Reliability and validity of this tool is determined through application of a pilot study andpanel of experts. Data were analyzed through the application of descriptive statistical (frequencies andpercentages), inferential statistical (mean of score), and logistic regression.Results: The Overall results revealed that the quality of life in colorectal cancer patients with psychologicalproblems was acceptable, and there is significant correlation between the psychological problems related forthese patients and one demographic characteristic that was region (residency) of patients.Recommendations: The study recommended to preparation of an education program for patients withcolorectal cancer and to raise awareness and education among families of patients to provide a betterpsychological life for their patients.